Household Moderation as a Foundation for Building a Harmonic Family: An Integration of Murray Bowen's Family Systems Theory and Maqashid Sharia - Sugitanata, Arif (Fakultas Syariah Institut Agama Islam Negeri Palu, 2024)
This study explores the concept of